Comparative Analysis of DES-Brown and DES-Holt Methods in Forecasting the Stock Price of PT Telekomunikasi Indonesia Tbk - Dela Juliarsih Rahman; Wiwit Pura Nurmayanti; Thesya Atarezcha Pangruruk; Erlyne Nadhilah Widyaningrum; Siti Hadijah Hasanah (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2026)
This study aims to dermine the best forecasting method for the stock price of PT Telekomunikasi Indonesia Tbk using the Double Exponential Smoothing (DES) Brown and DES-Holt methods. The data used consist of stock prices from January 2019 to September 2025. The DES-Brown method employs a single parameter, while DES-Holt uses two parameters. Forecasting accuracy is evaluated using Mean Absolute Deviation (MAD), Root Mean Squared Error (RMSE), and Mean Absolute Percentage Error (MAPE). The results indicate that the DES-Brown method with a smoothing parameter produces the smallest forecasting errors compared to the DES-Holt method, with MAD, RMSE , and MAPE . Therefore, it can be concluded that the DES-Brown method is the most suitable approach for forecasting the stock price of PT Telekomunikasi Indonesia Tbk.